The prior DNA paternity testing to determinate the identity of the child. The importance of the order of filiation in the Judicial Determination of Out-of-Wedlock Paternity: prior, clear and simple - Rimachi Huaripaucar, Hugo (2020)
This study analyzes some cases when the defendant is obligated to realize the DNA paternity testing into the context to determinate the identity of the child into judicial process. The different legal reforms in the Extramarital Paternity Judicial Filiation Process have created changes in compliance with the law: now, once again, the plaintiff filed the lawsuit and notified him, ten days later, the DNA test will be paid and performed by the accused. Only this test serves to determine his innocence: if he did not take the test, the court will declare paternity However, despite the legal reforms mentioned the problem respect to determinate the paternity persists: opposing the declaration of paternity is insufficient. Cases in which the accused does not take the necessary steps to obtain the biological evidence are analyzed. For example, the failure to pay for  the test within the expected period: partial payment when it is a fractional payment or when the defendant reclaims legal aid, and another cases. In other cases, Legal Practices use quick fixes or delay Legal Instruments. In both cases, they created injustice for the accused and did not protect the Child’s right to Identity Consequently, I believe that it is necessary to create Jurisprudential Precedents that limit this new Legal Design and its Legal Practices. Additionally, it is important to redesign this legal performance toobtain the Biological Test.